Analisis Kualitas Daging Kerbau dan Daging Sapi Menggunakan Uji pH, Daya Ikat Air, dan Uji Eber - Suci Rahmi; Asrul Asrul; Lia Angraeni; Mirza Angriawin; Hasanuddin Husin (JASATHP: Jurnal Sains dan Teknologi Hasil Pertanian, 2026)
Buffalo meat and beef are animal foods that have high nutritional value. Meat has complete nutritional content such as animal protein, air, energy, vitamins and minerals. By consuming buffalo meat or beef can fulfill nutritional balance so that the body's needs are met. The quality of meat varies according to the standardization of each slaughterhouse. This study was designed using a Completely Randomized Design design with 4 sampling times and five replications. This study is a survey and laboratory examination study using pH analysis test methods, air binding capacity, Eber test. Based on the results of the research that has been done, the pH test results of buffalo meat have an average of 6.70-6.84 and beef has an average value of 6.10-6.16. This shows that beef meets the SNI with a meat pH value ranging from 6.12-6.71 while buffalo meat has not met the specified SNI. The results of the water holding capacity (DA) test for buffalo meat averaged 42.57-46.58, while beef averaged 64.70-66.02. The absence of white dew in the Eber test indicates that the beef and buffalo meat are of good and safe quality. The quality of buffalo and beef meat has been handled properly, resulting in good and safe quality meat.